A cooperative venture capital framework : an innovation pipeline developed with an enterprise engineering approach that supports and promotes entrepreneurial teams in commercialising intellectual property and technology - Pretorius, Mathys A. (Stellenbosch : Stellenbosch University, 2017)
Thesis (MEng)--Stellenbosch University, 2017.